Pengaruh Live Streaming Terhadap Product Knoeledge Dcelup Chicken Crispy - Muria Abdul Hamid; Rindana Intan Emeilia; Siti Qona'ah (CV. ITTC INDONESIA, 2025)
Live streaming has become one of the leading features on social media platforms, including TikTok, and is now widely utilized by businesses to promote their products directly and interactively. One local culinary brand, Dcelup Chicken Crispy, takes advantage of this feature to enhance product appeal and consumer knowledge. This study aims to determine the extent to which TikTok live streaming influences the product knowledge of Dcelup Chicken Crispy’s followers.The research is grounded in the Stimulus-Organism-Response (S-O-R) theory, which explains that a stimulus (in this case, live streaming) can influence the organism (followers) and generate a response (product knowledge). This study employed a quantitative method with purposive sampling. A total of 100 respondents, who follow the official TikTok account of Dcelup Chicken Crispy, participated by filling out a questionnaire.The results show that Dcelup Chicken Crispy's TikTok live streaming has a 74% influence on product knowledge, while the remaining 26% is affected by other factors not examined in this study.